Zgodnja medicinska rehabilitacija po operaciji tumorjev osrednjega živčevja - Kos, Nataša (Rehabilitacija (Ljubljana), 2008)
Survival rates in patients with malignant brain tumors have increased due to early diagnostics, up-to-date multidisciplinary treatment and use of new medications. An individual's wish, however, is not only survival but also the quality of life. The latter can be much contributed to by rehabilitation which needs to be adjusted to the individual's abilities. In order to reach the established goals, medical rehabilitation needs to start early enough. Its procedures are aimed mainly at the prevention of complications, which at a later stage could have an adverse effect on the final functional outcome. Appropriately selected rehabilitation procedures can often help us to achieve patients' independence in mobility and basic activities of daily living already during their hospitalization. However, after the treatment has been concluded, the patients frequently need complex rehabilitation programs carried out at the Institute for Rehabilitation, Republic of Slovenia.
Keywords: medicinska rehabilitacija; možgani; rak (medicina); živčevje